Impact of edible and non-edible biodiesel fuel properties and engine operation condition on the performance and emission characteristics of unmodified DI diesel engine. Issue 3 (3rd May 2016) - Ashraful, A.M.; Masjuki, H.H.; Kalam, M.A.; Rashedul, H.K.; Habibullah, M.; Rashed, M.M.; Mosarof, M.H.; Arslan, A.
ABSTRACT: The purpose of this work is to test the feasibility of biodiesel as a substitute for diesel used in a direct injection (DI) diesel engine. The biodiesel was produced by an esterification and transesterification process. Experiments were conducted with diesel–biodiesel blends containing 10 and 20% biodiesel with the diesel fuel. The results of the biodiesel blends are compared with baseline diesel which was assessed at constant speed in a single cylinder diesel engine at various loading conditions. The physicochemical properties of palm and Calophyllum inophyllum biodiesel and their blends meet the standard specification ASTM D6751 and EN 14214 standards. The maximum brake thermal efficiency was attained with diesel fuel, 10% palm biodiesel (PB10) and 10% C. inophyllum biodiesel (CI10) at all load condition except low load condition. Engine emission results showed that the 20% C. inophyllum with 80% diesel blend exhibited 6.35% lower amount of brake specific carbon monoxide, and the PB20 blend and CI20 blend reduced brake specific hydrocarbon emission by 7.93 and 9.5%, respectively. NOx emission from palm and C . inophyllum biodiesel blends are found to be 0.29–4.84% higher than diesel fuel. The lowest smoke intensity is found at 27.5% for PB10 and CI10 biodiesel blends compared with diesel fuel.